Physical, cognitive, and social triggers of symptom fluctuations in people living with long COVID: an intensive longitudinal cohort studyResearch in context - Darren C. Greenwood; Maedeh Mansoubi; Nawar D. Bakerly; Aishwarya Bhatia; Johnny Collett; Helen E. Davies; Joanna Dawes; Brendan Delaney; Leisle Ezekiel; Phaedra Leveridge; Ghazala Mir; Willie Muhlhausen; et al. (Elsevier, 2024)
Summary: Background: Symptom fluctuations within and between individuals with long COVID are widely reported, but the extent to which severity varies following different types of activity and levels of exertion, and the timing of symptoms and recovery, have not previously been quantified. We aimed to characterise timing, severity, and nature of symptom fluctuations in response to effortful physical, social and cognitive activities, using Ecological Momentary Assessments. Methods: We recorded activity, effort, and severity of 8 core symptoms every 3 h for up to 24 days, in cohorts from both clinic and community settings. Symptom severities were jointly modelled using autoregressive and moving average processes. Findings: Consent was received from 376 participants providing ≥1 week's measurements (273 clinic-based, 103 community-based). Severity of all symptoms was elevated 30 min after all categories of activity. Increased effort was associated with increased symptom severity. Fatigue severity scores increased by 1.8/10 (95% CI: 1.6-1.9) following the highest physical exertions and by 1.5 (1.4-1.7) following cognitive efforts. There was evidence of only mild delayed fatigue 3 h (0.3, 0.2-0.5) or one day later (0.2, 0.0- 0.5). Fatigue severity increased as the day progressed (1.4, 1.0-1.7), and cognitive dysfunction was 0.2 lower at weekends (0.1-0.3). Interpretation: Cognitive, social, self-care and physical activities all triggered increased severity across every symptom, consistent with associated common pathways as potential therapeutic targets. Clear patterns of symptom fluctuations emerged that support more targeted self-management. Funding: National Institute for Health and Care Research.